Integration of Pintu Lestari Indonesia (Pitaria): Building Indonesia Cultural Awareness through the Implementation of the Use of Teaching Media for Teachers at IGTKI Pesawaran Regency - Ferly Ardhy; Fitra Endi Fernanda; Ulfa Isni Kurnia; Rahelia Hidayat; Nadia Setiani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
This activity aims to improve the abilities and skills of teachers who are members of Ikatan Kindergarten Teachers – Persatuan Teachers Republik Indonesia (IGTKI-PGRI) in Pesawaran Regency in creating and developing innovative teaching media, introduce regional culture through more innovative learning media, making the process of introducing culture more interesting and attractive for students. This community service program is carried out in the form of training to groups (IGTKI-PGRI) of Pesawaran Regency. Activities were carried out by socialization about innovative learning media conducted by Aisyah Pringsewu University Lecturers, Training on Skills in making Pintu Lestari Indonesia (PITARIA) teaching media using makeshift materials to produce interesting learning media, implementing the use of PITARIA teaching media in the classroom directly to see students' interest in PITARIA teaching media. This training results in an increased understanding of the use of creative and innovative teaching media, as well as improving teacher skills in making interesting and innovative learning media to make learning about culture easier for students to understand. The program's sustainability could be a limitation if there is no plan in place for ongoing support, training, or resource provision after the initial program period. This community service program can provide results by its initial purpose, which is to help improve teacher skills in making teaching media, and introduce regional culture.